NILAI-NILAI PENDIDIKAN KARAKTER PADA TAYANGAN ANIMASI RIKO THE SERIES SEASON 3 - Mukti, Muhammad Akbar (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2025)
The character of Indonesian children faces significant challenges in the digital era and Society 5.0. This study aims to: (1) identify the character education values present in the animated series Riko The Series Season 3; (2) examine character development within the series; (3) analyze the characterizations of Riko and other supporting characters; and (4) determine how the series influences character education values. This research employs a qualitative descriptive technique. The findings reveal several key aspects: (1) Riko The Series Season 3 incorporates fundamental character education values, including patience, sincerity, compassion, gratitude, religiosity, curiosity, broad-mindedness, appreciation for achievement, creativity, and social care. (2) Character development in the series is implemented through educational themes, exemplary role modeling, motivation, and habituation. (3) Specifically, the characterizations are defined as follows: (i) Riko exhibits patience, sincerity, compassion, religiosity, high curiosity, creativity, and social care; (ii) Qio represents creativity and extensive intelligence; (iii) the Father figure demonstrates appreciative behavior and a broad perspective; and (iv) the Mother figure embodies compassion, appreciation, and social concern. (4) The series influences character education principles through positive character modeling, moral instruction, cooperation, empathy, self-confidence, motivation, and social-emotional learning.